Subacute thyroiditis presenting as acute psychosis: a case report and literature review - Lee, Kyung Ae (The Korean Association of Internal Medicine, 2013)
We describe herein an unusual case of subacute thyroiditis presenting as acute psychosis. An 18-year-old male presented at the emergency department due to abnormal behavior, psychomotor agitation, sexual hyperactivity, and a paranoid mental state. Laboratory findings included an erythrocyte sedimentation rate of 36 mm/hr (normal range, 0 to 9), free T4 of 100.0 pmol/L (normal range, 11.5 to 22.7), and thyroid stimulating hormone of 0.018 mU/L (normal range, 0.35 to 5.5). A technetium-99m pertechnetate scan revealed homogeneously reduced activity in the thyroid gland. These results were compatible with subacute thyroiditis, and symptomatic conservative management was initiated. The patient's behavioral abnormalities and painful neck swelling gradually resolved and his thyroid function steadily recovered. Although a primary psychotic disorder should be strongly considered in the differential diagnosis, patients with an abrupt and unusual onset of psychotic symptoms should be screened for thyroid abnormalities. Furthermore, transient thyroiditis should be considered a possible underlying etiology, along with primary hyperthyroidism.